Does community-based health insurance reduce disparities in modern health service utilization among households in Ethiopia? A community-based comparative cross-sectional study - Edosa Tesfaye Geta; Edosa Tesfaye Geta; Abebe Wakjira Bidika; Belachew Etana (Frontiers Media S.A., 2023)
BackgroundCommunity-based health insurance (CBHI) is an emerging and promising concept to access affordable and effective healthcare by substantially pooling risks to improve health service utilization (HSU) and equity. While there have been improvements in healthcare coverage in Ethiopia, disparities in healthcare remain a challenge in the healthcare system. Hence, the study aimed to assess the effects of CBHI on the reduction of disparities in modern health service (MHS) utilization among households.MethodsA community-based comparative cross-sectional study was conducted between 1 February and 30 April 2022 among households in the Gida Ayana district, Ethiopia. The sample size of 356 was determined using the double population proportion formula, and participants were selected using multistage sampling. Data were entered into EpiData 4.6 and exported to SPSS 25 for analysis.ResultsAmong 356 households, 321 (90.2%) reported that at least one member of their family fell ill in the previous 6 months; 153 (47.7%) and 168 (52.3%) households were among the insured and uninsured, respectively. Only 207 [64.5, 95% confidence interval (CI) = 59.0-69.7%] of them utilized health services. The level of MHS was 122 (79.7, 95% CI = 75.5-85.8%) and 85 (50.6, 95% CI = 42.8-58.4%) among insured and uninsured, respectively. Insured households were four times more likely to utilize MHS compared to uninsured households [adjusted odds ratio (AOR) = 4.27, 95% CI = 2.36-7.71]. Despite the households being insured, significant disparities in MHS utilization were observed across the place of residence (AOR = 14.98, 95% CI = 5.12-43.82) and education level (AOR = 0.20, 95% CI = 0.05-0.83).ConclusionOverall, the CBHI scheme significantly improved the level of MHS and reduced disparities in utilization across wealth status and family size differences. However, despite households being insured, significant disparities in the odds of MHS utilization were observed across the place of residence and education level. Hence, strengthening the CBHI scheme and focusing on the place of residence and the education level of households are recommended to improve MHS utilization and reduce its disparities.